Konsep Manusia Ideal Seyyed Hossein Nasr dan Relevansinya dengan Pengembangan Karakter Masyarakat Modern Indonesia - Yusuf, Moh Asror (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2016)
This study aims at explaining the concept of ideal human proposed byHossein Nasr in relation to concept of ideal human in Indonesia today.Efforts to create the ideal man is very urgent in humanitarian crisis today.This should be based upon whole concept, therefore it is necessary tosynthesize the concept of ideal human. Hossein Nasr is one of the scientistswho is very concerned about crisis of modern man. This is a libraryresearch using content analysis and history. The study states that the idealman is the man whose three parts (body, mind, and soul) are integrated asa whole. Such integration must consider vertical dimensions of man to theSupreme Reality (God). If man is actively connected with the Lord then hewill not be alienated from himself, his environment and his Lord. Nasrconcept is certainly in line with the concept of human development asstipulated in the Act. No. 20 of 2003, and Development Plan 2010-2014,that national education should be able to develop and integrate thye threeimportant parts of human.